2019
DOI: 10.3390/su11205787
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Satisfaction and its Influencing Factors in the Policy of Economic Compensation for Cultivated Land Protection: A Case Study in Chengdu, China

Abstract: With the rapid progress of urbanization, the loss of cultivated land has attracted great attention worldwide, and economic compensation is one of the incentives commonly used by the governments to enhance farmers’ enthusiasm in protecting cultivated land. In recent years, although various economic compensation modes have been implemented by the Chinese government, such modes are still experimental and exploratory. Thus, designing and implementing a national economic compensation mode is urgent to effectively p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…Education, cultivated area [77], years of experience and mobility (access to transport) were the factors responsible for maximizing the farmers' satisfaction, i.e., in the second tier.…”
Section: Grand Total 100mentioning
confidence: 99%
“…Education, cultivated area [77], years of experience and mobility (access to transport) were the factors responsible for maximizing the farmers' satisfaction, i.e., in the second tier.…”
Section: Grand Total 100mentioning
confidence: 99%
“…Capitanio et al (2011) also suggested that an increase in the extent of family labor on a farm would have an adverse effect on a peasant farmers participation in cultivated land protection programs. Furthermore, farmers' attitudes (Ruto and Garrod, 2009; Barreiro-Hurlé et al, 2010), information available regarding the policy (Wilson and Hart, 2000), and farmers' satisfaction (Xiao et al, 2019) might affect farmers' overall participation. Hence, it is of great significance to discuss farmers' behavior and its driving factors, which may have a direct impact on the extent of farmers' participation in cultivated land protection .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 17 provincial governments in China expressed an interest in operating such schemes (Zhu et al, 2018). Through the analysis of satisfaction, Xiao et al (2019) found that farmers' satisfaction with the cultivated land protection fund was not very high on the whole. Based on the comparison of the three compensation models in Chengdu, Wuhan and Suzhou, Zhu et al (2018) proved that the implementation effect of the Chengdu model with pension insurance as the highlight was the best.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have conducted extensive research on improving the implementation of CLPP, mainly focusing on the influence of factors, such as individual or family characteristics of farmers, livelihood capital, degree of concurrent employment, interest statement, consciousness differentiation, cognitive level, and satisfaction degree on the implementation of CLPP [16][17][18]. Some scholars have also researched institutional changes, regional differences, and nonmarket value [19,20].…”
Section: Introductionmentioning
confidence: 99%